Democracy under Algorithmic Power: Governmentality and Control in The Digital Public Sphere - Izza Amalia; Ade Candra Sutrisna; Tutik Sulistyowati (Indonesian Journal of Innovation Multidisipliner Research, 2026)
The development of digital spaces has transformed digital platforms into new public arenas that significantly influence the dynamics of democracy in Indonesia. The high use of the internet and social media creates substantial opportunities for public participation, while also presenting challenges in the form of inaccurate information dissemination, polarization, and the influence of algorithmic mechanisms on public opinion formation. This study aims to analyze how digital platform algorithms affect democratic processes through the regulation of information flows, the formation of user behavior, and the construction of digital public spaces. This research employs a qualitative literature-based approach by analyzing secondary data from scientific articles, national and international institutional reports, and digital platform policy documents. The analysis applies Michel Foucault’s concept of governmentality to understand algorithms as mechanisms of power that operate through regulation, surveillance, normalization, and knowledge production. The findings indicate that algorithms play a dual role in digital democracy. Algorithms can expand political participation, support information dissemination, and provide spaces for public engagement; however, they may also reinforce misinformation, polarization, and limitations on diverse perspectives through content curation mechanisms. This study concludes that strengthening digital democracy requires algorithmic transparency, improved digital literacy, and collaboration among governments, digital platforms, academics, and civil society to establish an inclusive and sustainable digital public sphere.